Aplikasi Pembelajaran Pengenalan Budaya Indonesia pada Mobile Device Berbasis Android - Rendrahadi Rendrahadi; Andreas Handojo; Alexander Setiawan (Jurnal Infra, 2017)
Indonesia is a country that has a wealth of diverse cultures spread from Sabang to Merauke. Although the government has included a lesson about Indonesian culture in subjects Art and Culture, but there are still a lot of the general public as well as students who do not know the form and name of the tribe, traditional houses, traditional clothing, folk songs, traditional foods, local weapons, and musical instruments regions in Indonesia.Therefore, a learning application was created that utilizes mobile learning technology. By using mobile learning then the user can access learning content without being tied to space and time so that it can be accessed at any time with interesting illustration. Budaya Bangsa Kita Application is made useful to help users in learning the introduction of Indonesian culture that provides the knowledge with illustrations in the form of images, audio, text and video. This application also can to learn, answer quiz, view a gallery of images and video and a puzzle game. The result is an application that can provide knowledge to the user so as to know the culture in Indonesia through the illustrations provided.